Prevalence of Gastrointestinal Endoparasites in Free-Range Chicken at Traditional Market Payakumbuh - Ilahi, Yusra; Zelpina, Engki; Putri, Ii Amelia; Sujatmiko; Amir, Yurni Sari; Suliha (Universitas Airlangga, 2024)
Background: Worm infections in free-range chickens are an important health issue in the animal food industry and consumption in Indonesia. Purpose: This study aims to determine the prevalence of worms in the intestines of free-range chickens sold in traditional markets in Payakumbuh City, and to identify their types. Method: Worm identification was carried out using samples of chicken intestines from traditional markets in Payakumbuh City. The samples were taken to the laboratory to be dissected to check for the presence of worms in the intestines. Intestines that were positive for worms were placed in a petri dish containing distilled water before being placed in a plastic bottle containing 70% ethanol. The method used for staining was Acetocarmine Semichon for cestodes and clove oil for nematodes. Worm species was determined by observation under a microscope. Data in the form of the types of worms found was analyzed descriptively. Data obtained quantitatively, namely the prevalence of endoparasites, was processed using Ms. Excel 2013. Results: The results showed that 31 out of 50 samples of free-range chicken intestines (Gallus domesticus) examined in traditional markets in Payakumbuh City were positive for worm infections. The prevalence of worm infections in traditional markets in Payakumbuh City was found to be 62%. The prevalence based on the type of endoparasite in traditional markets in Payakumbuh City was Railletina sp. (28%), Hymenolepis sp. (6%), Ascaridia sp. (14%), and Hetarakis sp. (14%). Conclusion: The prevalence rate of worm infections in free-range chickens in traditional markets in Payakumbuh City was 62%. The types of worms found were Railletina sp., Ascaridia sp., Hetarakis sp., and Hymenolepis sp. The most common type of worm was Railletina sp.